(3QHj GdSdGes - (3GOGf, YGFTIs; (3GdZGfe, MhQs; (3YcGhj, QMGHs; (3cfYGf, CMeOs ((3GdOGQ GdHjVGA, GdeZQHs (3OGQ GdKbGaI ddfTQ hGdJhRjYs, 2024)
(3GdSdGe jYfj GdSGde ef cd fbU hBaI hYjH, dG JCNPg SfI hdG fhe(B. (3afMf GdHTQ ceG YdeJ feQV hfJYH hffYS hffGe hJUjHfG GdBaGJ, CeG Gddg agh GdSdGe GdSGde ef cd Pdcs
(3JQHjI OjfjIs
Keywords: (3GdOjfs